Using a Technology-Based Graphic Organizer to Improve the Planning and Persuasive Paragraph Writing by Adolescents With Disabilities and Writing Difficulties. (February 2022) - Brady, Kelly K.; Evmenova, Anya S.; Regan, Kelley S.; Ainsworth, Melissa K.; Gafurov, Boris S.
A multiple-probe design was used to investigate planning and persuasive paragraph writing by three secondary students with disabilities and writing difficulties. The intervention consisted of one-on-one explicit instruction in persuasive writing and the use of a technology-based graphic organizer (TBGO) with embedded strategies and supports. Dependent variables included the number of sentences and overall holistic writing quality. The results were mixed. Two adolescents with the primary diagnosis of learning disabilities improved their writing performance when using the TBGO and remained above baseline levels when the TBGO was removed. One more participant diagnosed with autism demonstrated modest changes in the quantity and quality of his writing. Students reported positive perceptions of the TBGO, indicating a socially valid intervention. Implications, limitations, and directions for future research are discussed.